Важливість розвитку ринку аграрного страхування для національної економіки - Slobodianiuk, Olga; Lositska, Tetyana; Pukała, Ryszard (Dr. Viktor Koval, 2018)
Introduction. The state and its agricultural support programs provide assistance to the victims, but this is not in line with world practice. Minimization of losses, which is formed at the expense of the reserve fund of the state budget, is based on outdated methods of the post-Soviet era. The emergence of a new number of subjects of the market of agro-insurance of all forms of ownership also does not have enough lifting for its development and covering losses from unforeseen weather conditions. The threat of bankruptcy, fierce competition, prompts entrepreneurs to apply new market-based methods for reimbursing potential costs and doing business. Thus, insurance of agricultural products and their further development will lead to the solution of the current urgent problem of agro companies to cover losses from unforeseen natural disasters and natural disasters, and will provide the reliability, solvency and financial independence of each company in this business. Aim and tasks. The purpose of the article is to consider the theoretical foundations for the development of the insurance market of agri-insurance and its importance. Results. The agri-insurance market plays an important role in the national economy of the Ukrainian state, and therefore needs further development, increased attention from both the state and the scientists of the insurance industry. Without agrarian insurance, the Ukrainian agricultural sector is not possible, because every year losses from weather conditions are occurring, which leads to a shortage of gross crops and significant losses.The article reveals the basic concepts of agri-insurance. Conducted competitive competitive analysis and statistical survey of agri-insurance market in recent years. The ways of development of the market of agrarian insurance are offered. Conclusions. The national agro-insurance market is slowly developing, although more and more agricultural enterprises trust insurers. Competition in the insurance market provides fair competition among them in order to receive new customers, but not enough to generate more profits and development in general. The analysis of key indicators of the market shows that there is development, but it is insignificant, therefore, it is necessary to take measures on the basis of foreign experience and to submit proposals for further development. Such proposals may include: strengthening system support from the Government of the country and improving its regulation, developing new insurance products, which will increase competition among insurance companies, increase index insurance, and so on. Thus, the introduction, based on world practice, of new approaches to the development of agrarian insurance, will provide Ukrainian farmers with opportunities to prevent financial losses in the event of unforeseen events.